2021
DOI: 10.1002/jum.15816
|View full text |Cite
|
Sign up to set email alerts
|

The Added Value of a Computer‐Aided Diagnosis System in Differential Diagnosis of Breast Lesions by Radiologists With Different Experience

Abstract: Objectives-To evaluate the value of the computer-aided diagnosis system, S-Detect (based on deep learning algorithm), in distinguishing benign and malignant breast masses and reducing unnecessary biopsy based on the experience of radiologists.Methods-From February 2018 to March 2019, 266 breast masses in 192 women were included in our study. Ultrasound (US) examination, including S-Detect technique, was performed by the radiologist with about 10 years of clinical experience in breast US imaging. US images were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…We extracted and summarized the basic characteristics of the included literature. Four included studies were prospective ( 20 , 21 , 23 , 26 ), seven were retrospective ( 18 , 19 , 25 , 29 - 31 , 33 ), and the remaining articles were not reported. Also, a total of 3,349 patients with 3,895 lesions were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We extracted and summarized the basic characteristics of the included literature. Four included studies were prospective ( 20 , 21 , 23 , 26 ), seven were retrospective ( 18 , 19 , 25 , 29 - 31 , 33 ), and the remaining articles were not reported. Also, a total of 3,349 patients with 3,895 lesions were included.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the diagnostic performance was high in both groups; pooled sensitivity, the pooled specificity and AUC were all higher in the senior radiologist group than in the junior radiologist group, and the AUC value was significantly different between the two groups (P<0.01). Some articles showed that the improvement was more significant in the junior radiologist group compared to US (19)(20)(21)23). Meanwhile, we analyzed the clinical application value of US + S-detect by plotting Fagan diagrams, setting the pre-test probability at 50% and the post-test probability at 87% and 81% for the senior and junior groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in medical diagnostics the evaluation of system accuracy, and accordingly its trustworthiness, may require a comparison with how well human experts typically perform in the same task. Whereas a novice user will perform significantly worse without the system, an expert user might perform better without the system [113]. Consequently, if a user assesses the trustworthiness of a system by referring to the individual standard: "Will the system provide better outcomes than I would?…”
Section: Actual Trustworthiness (At)mentioning
confidence: 99%